2023
DOI: 10.3390/diagnostics13223422
|View full text |Cite
|
Sign up to set email alerts
|

Attention TurkerNeXt: Investigations into Bipolar Disorder Detection Using OCT Images

Sermal Arslan,
Mehmet Kaan Kaya,
Burak Tasci
et al.

Abstract: Background and Aim: In the era of deep learning, numerous models have emerged in the literature and various application domains. Transformer architectures, particularly, have gained popularity in deep learning, with diverse transformer-based computer vision algorithms. Attention convolutional neural networks (CNNs) have been introduced to enhance image classification capabilities. In this context, we propose a novel attention convolutional model with the primary objective of detecting bipolar disorder using op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…By assessing the functional integrity of the brain, electroencephalography (EEG) may reveal potential distinctions between BPD and BD. However, no conclusive evidence exists for whether the two disorders can be differentiated by EEG features [ 5 , 7 12 ]. Nonetheless, studies have reported specific EEG findings in patients with BPD, such as intermittent rhythmic delta and theta activity observed during severe dissociative states characterized by inner tension and auto aggressive behaviour [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…By assessing the functional integrity of the brain, electroencephalography (EEG) may reveal potential distinctions between BPD and BD. However, no conclusive evidence exists for whether the two disorders can be differentiated by EEG features [ 5 , 7 12 ]. Nonetheless, studies have reported specific EEG findings in patients with BPD, such as intermittent rhythmic delta and theta activity observed during severe dissociative states characterized by inner tension and auto aggressive behaviour [ 13 ].…”
Section: Introductionmentioning
confidence: 99%